Social Support from Nursing Students to Their Mother in Implementation of BSE - Nehemia Simanjuntak; Ida Maryati; Valentina B.M. Lumbantobing (Media Karya Kesehatan, 2021)
Breast cancer is one type of cancer in a woman with the highest incidence globally, including Indonesia. Early detection, such as breast self-examination (BSE), can find breast cancer early, thus can reduce mortality and morbidity. BSE behavior is influenced by many factors of social support. Social support can come from the community, health workers, friends, and families, such as parents, spouses, and children. This study aims to determine social support from nursing students to their mothers to implement breast self-examination (BSE). This study was a quantitative descriptive design. This study's population was active students of batch 2016 and 2017 of Nursing Faculty, Universitas Padjadjaran in Jatinangor, Garut, and Pangandaran region. The sampling method used a purposive sampling of 236 students of Nursing Faculty, Universitas Padjadjaran. The data was collected using a social support questionnaire about BSE. Data analysis was used univariate as follows frequency distribution and percentage. This study has three levels of social support: high, moderate, and low. The results showed that social support had a high level of 36.86% and a low level of 35,59%. Students had a high level of emotional support (40,25%), instrumental support (20.76%), information support (52.54%) and appraisal support (75,42%). The study has indicated that social support by nursing students had still low. This can be improved by changing perceptions and increasing awareness about BSE. Keywords: Breast self-examination (BSE); mothers; social support; students.